Rancang Bangun Sistem Validasi Surat Akademik Menggunakan QR Code dan Algoritma AES pada Siakadbeta Universitas Halu Oleo - La Surimi; Adha Mashur Sajiah; Natalis Ransi, Jumadil Nangi; L.M. Bahtiar Aksara; Rizal Adi Saputra (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2023)
Abstract — Letters are an important part of administration at a university. Letters are a formal means of communication between internal institutions within a university. In the academic process at Halu Oleo University, letters are generally used for applications for academic dispensation, for example KRS dispensation requests, uploading repair grades and UKT payment dispensations. This letters is still carried out in a conventional way so it is still difficult to validate the integrity of the letter, even though the letter contains a stamp or signature of the head of the institution. Therefore, in this study a validation system for academic letters was developed using the QR Code and the AES Algorithm. The AES algorithm is used to ensure document data integrity. While the QR Code is used so that the validation process is easily carried out by the user. The results of testing with the black box showed that the results of the implementation of the system design can run effectively. Whereas in testing the performance of the data validation process it showed that when the number of attachments is 25, the results of the QR Code cannot be scanned. This is due to the density of the contents of the QR Code and the scanning tool used. Keyword — AES Algorithm, Document Validation, QR Code, and Rational Unified Process, and Document Validation.